Optimized model potential parameters in metals - Ese, Osman; Reissland, J. A. (IOP Publishing, 1973)
The Heine-Abarenkov model potential for metals was developed by Shaw (1968) to avoid arbitrary choice of the model radius. Here the parameters have been calculated for a large number of the metallic elements in each case including selfconsistent iteration through the calculated shifted Fermi level. The expressions used in the calculations are discussed and results are presented of the Fermi level calculations together with selfconsistent optimized model potential parameters and their energy derivatives.